2017
DOI: 10.1063/1.5004248
|View full text |Cite
|
Sign up to set email alerts
|

Layer-sensitive magneto-optical Kerr effect study of magnetization reversal in Fe/MnAs/GaAs(001)

Abstract: Fe/MnAs/GaAs(001), a prototypical system for thermally assisted magnetization reversal, is studied by magneto-optical Kerr effect measurements. The results show that it is possible to recover elemental sensitivity from magneto-optical measurements when both Kerr rotation (θK) and Kerr ellipticity (ϵK) are measured under the same conditions. Both Fe and MnAs magnetic cycles can be extracted from simple linear combinations of θK and ϵK cycles. The data analysis shows that the orientation of the Fe magnetization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…12 However, in some contexts, a complete characterization of the final polarization is essential to gather an accurate understanding of the magnetic state of the system. 13,14 In particular, in the ultrafast magnetism community, research is ongoing to untangle the magnetic dynamics from charge dynamics, which may also affect the signal when the electronic system is strongly out of equilibrium. [15][16][17] In this prospect, studies have shown that both the Kerr rotation and the Kerr ellipticity must be retrieved in order to relate the measurement to the magnetization as each of these quantities alone offers incomplete information.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, in some contexts, a complete characterization of the final polarization is essential to gather an accurate understanding of the magnetic state of the system. 13,14 In particular, in the ultrafast magnetism community, research is ongoing to untangle the magnetic dynamics from charge dynamics, which may also affect the signal when the electronic system is strongly out of equilibrium. [15][16][17] In this prospect, studies have shown that both the Kerr rotation and the Kerr ellipticity must be retrieved in order to relate the measurement to the magnetization as each of these quantities alone offers incomplete information.…”
Section: Introductionmentioning
confidence: 99%
“…A 70-nm thick MnAs epitaxial film was grown by molecular beam epitaxy on GaAs(001) [23]. The epitaxial relationship with c [001] GaAs and a [110] GaAs was checked by laboratory x-ray diffraction measurements.…”
mentioning
confidence: 99%